Hubungan Persepsi Latihan Dengan Kepuasan Kerja Di Kalangan Guru-Guru Koperasi Sekolah-Sekolah Menengah Zon Sentul, Wilayah Persekutuan : Satu Kajian Emperikal - Nor Aishah, Abdullah (1997)
This emperical study was conducted among the co-operative teachers at 11 secondary schools in Sentul Zone, Wilayah Persekutuan. The main aim of this research is to investigate; (i) perception of adequate training and job satisfaction; (ii) perception of beneficial training and job satisfaction, (iii) demographic factors that have significant relationship with job satisfaction, (iv) the level of job satisfaction among the cooperative teachers, and (v) to detect the predictors of job satisfaction. Questionnaire was constructed based on the measurement suggested by; (I) Koning, 1993, which focused on 6 items on adequate training, (ii) Garavan and Cinneide, 1994, which consists of 12 items on beneficial training, and (iii) 15 items on job satisfaction by Chalykoff and Kochan, 1989. Selected demographic factors analysed are age, gender, academic qualification, working experience, teaching periods, performance appraisal and rewards. Research findings showed that; (i) there is a positive and significant relationship between beneficial training and job satisfaction, (ii) teaching periods a negative and significant relationship with job satisfaction, and (iii) there is a difference in job satisfaction among the co-operative teachers. Other hyphotheses testing are not significant and are not supported. Finally, researcher would like to make recommendations to the administrators which are; (i) to give full commitment to the co-operative activities without depending totally on Jabatan Pembangunan Koperasi, and (ii) it is an advantage to apply Strategic Management techniques to improve the work and the school co-operative performance.